A mouse model for spondyloepiphyseal dysplasia congenita with secondary osteoarthritis due to a Col2a1 mutation. - Esapa, C; Hough, T; Testori, S; Head, R; Crane, E; Chan, C; Evans, H; Bassett, J; Tylzanowski, P; McNally, E; Carr, A; Boyde, A; et al. (2012)
Progeny of mice treated with the mutagen N-ethyl-N-nitrosourea (ENU) revealed a mouse, designated Longpockets (Lpk), with short humeri, abnormal vertebrae, and disorganized growth plates, features consistent with spondyloepiphyseal dysplasia congenita (SEDC). The Lpk phenotype was inherited as an autosomal dominant trait. Lpk/+ mice were viable and fertile and Lpk/Lpk mice died perinatally. Lpk was mapped to chromosome 15 and mutational analysis of likely candidates from the interval revealed a Col2a1 missense Ser1386Pro mutation. Transient transfection of wild-type and Ser1386Pro mutant Col2a1 c-Myc constructs in COS-7 cells and CH8 chondrocytes demonstrated abnormal processing and endoplasmic reticulum retention of the mutant protein. Histology revealed growth plate disorganization in 14-day-old Lpk/+ mice and embryonic cartilage from Lpk/+ and Lpk/Lpk mice had reduced safranin-O and type-II collagen staining in the extracellular matrix. The wild-type and Lpk/+ embryos had vertical columns of proliferating chondrocytes, whereas those in Lpk/Lpk mice were perpendicular to the direction of bone growth. Electron microscopy of cartilage from 18.5 dpc wild-type, Lpk/+, and Lpk/Lpk embryos revealed fewer and less elaborate collagen fibrils in the mutants, with enlarged vacuoles in the endoplasmic reticulum that contained amorphous inclusions. Micro-computed tomography (CT) scans of 12-week-old Lpk/+ mice revealed them to have decreased bone mineral density, and total bone volume, with erosions and osteophytes at the joints. Thus, an ENU mouse model with a Ser1386Pro mutation of the Col2a1 C-propeptide domain that results in abnormal collagen processing and phenotypic features consistent with SEDC and secondary osteoarthritis has been established.